2018
DOI: 10.1007/s10029-018-1818-9
|View full text |Cite
|
Sign up to set email alerts
|

EHS clinical guidelines on the management of the abdominal wall in the context of the open or burst abdomen

Abstract: When considering the OA, dynamic closure techniques should be prioritized over the use of static closure techniques (strong recommendation). However, for techniques including suture closure, mesh reinforcement, component separation techniques and skin grafting, only clinical expertise guidance was provided. Considering the BA, a clinical expertise guidance statement was advised for dynamic closure techniques. Additionally, a clinical expertise guidance statement concerning suture closure and a good practice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 128 publications
4
56
0
9
Order By: Relevance
“…Nevertheless, there is a higher risk of SSO associated with synthetic mesh use in contaminated and infected operations. 50 Therefore, most surgeons are reluctant to use it under these conditions, and many authors consider its use contraindicated. [28][29][30] We recognize the need for additional studies involving emergency operations, especially under conditions of contamination or infection, but we believe that the benefit of preventing incisional hernia and FD outweighs the risk of SSO because the management of these complications is limited to bedside procedures in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a higher risk of SSO associated with synthetic mesh use in contaminated and infected operations. 50 Therefore, most surgeons are reluctant to use it under these conditions, and many authors consider its use contraindicated. [28][29][30] We recognize the need for additional studies involving emergency operations, especially under conditions of contamination or infection, but we believe that the benefit of preventing incisional hernia and FD outweighs the risk of SSO because the management of these complications is limited to bedside procedures in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has acted as methodological and content coordinators of landmark surgical guidelines and have served as members of surgical guideline development groups. [9][10][11][12][13][14] Even though members of our group, in their role as guideline developers, have made every effort to comply with the highest methodological standards, as indicated by adherence to Grading of Recommendations Assessment, Development and Evaluation (GRADE) and AGREE II methodologies, 15 16 we noticed that compliance with all aspects of several parameters of the AGREE II instrument was not possible. For example, the item 'The potential resource implications of applying the recommendations have been considered' may be difficult to be universally addressed.…”
Section: Need For An Agree II Extensionmentioning
confidence: 99%
“…Studies have shown that VAC-IPOM in patients with OA treatments decrease re-operations, duration of hospital and ICU stay, and the incidence of incisional hernia, when compared with VAWCM, which represents the current standard of care [45,46].…”
Section: What About the Open Abdomen Closure?mentioning
confidence: 99%